Contextualization of Theft Criminal Verse in Indonesian Positive Law - Candra, Marli; Najib, M. Ainun; Najib, M. Ainun (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
The widespread abandonment of Islamic Criminal Law reveals a significant lack of comprehensive understanding of its principles. Many legal systems operate under the assumption that they are entirely separate from Islamic law, yet Islamic thinkers have historically influenced various global legal systems, including the approach to punishment for theft. Thus, there is a need to contextualize Islamic Criminal Law to illustrate that it can adapt to modern times. This research employs a normative legal framework with a conceptual and comparative approach, focusing on the crime of theft as addressed in Islamic criminal law, Indonesian positive law, and Iranian positive law. The study concludes that these three legal systems share a common goal: to deter theft. However, the forms of punishment differ. Indonesian positive law primarily emphasizes imprisonment as the main consequence. In contrast, Islamic criminal law advocates for hand-cutting, intending to deter future criminal behavior. Iranian law, on the other hand, incorporates multiple levels of punishment, ranging from finger-cutting to imprisonment as a last resort. Ultimately, each legal system determines the appropriate sentence for theft based on the context of the crime, the offender's background, and the specific circumstances surrounding the event